Isolasi Dan Identifikasi Senyawa Metabolit Sekunder Ekstrak Etil Asetat Dari Kulit Batang Nangka - Dwi Agustini (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2018)
Artocapus is one of genus from Moraceae family plant. This plant is used by people as builing material (timber), food stuff (fruit) and traditional medicine (skin stem and leaf). In this particular research, has been isolated metabolism shift which is located toward Artocarpus heterophylla Lamk. Skin stem.one of pure molecules has boiling point about 177-178oC, positively react with Wagner reactor result brown sediment and Dragendroff reactor result orange sediment. It’s supported by solubility exam which this molecules couldn’t be soluble in n-hexana, methanol, ethanol, little bit soluble in choloroform and good in aseton with analysis KLT shown one tarnish in three eluen system with each valune have Rf 0,25 for n-hexana: chloform (6:4), 0,6 for n-hexana:ethyl acetat (6:4) and 0,8 for ethyl acetat:chloroform (6:4).